Electric sounds technological change and the rise of corporate mass media - Wurtzler, Steve J. (Film and culture, 2007)
Focuses on the innovations in the electronic production and transmission of sound in the 1920s and '30s and their explosive impact on the American mass media, especially the radio, the phonograph, and the cinema.